The THE FERFORMANCE ANALYSIS OF ELECTRIC CAR OF THE UNIVERSITY OF MATARAM : THE FERFORMANCE ANALYSIS OF ELECTRIC CAR OF THE UNIVERSITY OF MATARAM - I Gusti Ngurah Ketut Yudhyadi; Pandri Pandiatmi; Emmy Dyah S.; Ida Bagus Alit; Sinarep (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2025)
The university of Mataram car suspension and its control was designed to minimize the vibration produced by unwanted external inputs i.e., changes of road contours that reach the car passengers. This effort will provide the passenger with higher safety and comfort. In this study, a quarter car model with two degree of freedoms (2 DOF) was designed and developed its mathematical model. The effects of the road contour were studied and analyzed in term of overshoot and settling time that affect the main body, suspension as well as the passenger. The MATLAB Simulink model was programmed to mimic the behavior of the suspension and its response to the input which was the road contour (step function). This approach was very helpful to reduce the effort, time and money. The result shows that with implementation of the design parameters chose, the responses of the system (displacement and velocities) were satisfied the criteria of comfortable (there are no overshoot), however, the settling time was seconds that much higher than expected which will disturb the passenger comfort. This point shows that the suspension design needs further improvement with consideration of using active suspension with adequate control system.